Resultados perinatais em gestações com centralização de fluxo fetal ao estudo dopplervelocimétrico arterial - Vasconcelos, Rodney Paiva (2007)
Evaluate the perinatal results in pregnancies with fetal brain sparing on the Doppler velocimetric study and identify the main prognostic factors associated with neonatal death. Methods: it is a transverse study from the charts of pregnant women with diagnosis of brain sparing, absent or reversed end-diastolic flow in the umbilical artery, followed at the Service of Maternal-Fetal Medicine of Maternidade-Escola Assis Chateaubriand – Universidade Federal do Ceará. There were analyzed 143 patients with single pregnancies, without structural or chromosomal anomalies, presenting gestational age above 22 weeks and fetal weight equal or above 500 grams. ROC curve was constructed for gestational age and weight at birth (independent variables) and neonatal death (dependent variable). The perinatal results were evaluated on the general population and on each group (brain sparing, absent and reversed end-diastolic flow), later compared with each other. For the statistical analisys it was utilized the tests: Shapiro-Wilk, Levene, t Student, Mann-Whitney, ANOVA, Kruskal Wallis, Fisher, Chi-square, Logistical and Multinomial Regression. All were considered statistically significant when p < 0.05. Results: the majority of pregnant women (78.3%) presented some hypertensive disturb associated to the pregnancy. The pregnancy was resolved in the first 24 hours after Doppler velocimetric diagnosis on most cases (74.8%), being the abdominal access utilized in 96.5% of the times. At the moment of delivery, the average gestational age was 33.6 weeks and the weight was 1684g. The newborns were classified as small for gestational age in 69.6% and needed ICU admission in 63% of the cases. The indexes of perinatal mortality for brain sparing, absent and reversed end-diastolic flow were respectively 11.1, 31.1 and 70.6%. The weight of the newborn (area bellow the ROC curve 0.934, p=0.000) and gestational age at birth (area 0.909, p=0.000) have shown to be good predictors of neonatal death. The cutoff point calculated for the weight was 1010g and for the gestational age was 32.5 weeks. The incidence of diminished amniotic fluid index (AFI) in the pregnancies with lethal perinatal outcome was 41.2% and in those without lethality was 41.3%. Conclusions: fetuses with diagnosis of brain sparing, absent and reversed end-diastolic flow presented progressively worse and statistically different with each other prognosis. The gestational age and weight at birth showed excellent correlation with neonatal mortality. The AFI did not demonstrate association with lethality rate.